2011
DOI: 10.1039/c0ob00475h
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotidylation of unsaturated carbasugar in validamycin biosynthesis

Abstract: Validamycin A is a member of microbial-derived C7N-aminocyclitol family of natural products that is widely used as crop protectant and the precursor of the antidiabetic drug voglibose. Its biosynthetic gene clusters have been identified in several Streptomyces hygroscopicus strains, and a number of genes within the clusters have been functionally analyzed. Of these genes, valB, which encodes a sugar nucleotidyltransferase, was found through inactivation study to be essential for validamycin biosynthesis, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…No other NDP-valienols have previously been tested, because the corresponding nucleotidyltransferase enzyme VldB appeared to prefer GTP as substrate, and produces GDP-valienol (Yang et al, 2011). The preference of VldE toward GDP-valienol was also supported by its X-ray crystal structures (Cavalier et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No other NDP-valienols have previously been tested, because the corresponding nucleotidyltransferase enzyme VldB appeared to prefer GTP as substrate, and produces GDP-valienol (Yang et al, 2011). The preference of VldE toward GDP-valienol was also supported by its X-ray crystal structures (Cavalier et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we prepared all five possible NDP-valienols and evaluated the substrate preference of VldE – whether or not it can process other NDP-valienols. GDP-, ADP-, and CDP-valienols were prepared from valienol 1-phosphate and their corresponding nucleotidyl triphosphates (GTP, ATP, or CTP), using VldB (Yang et al, 2011), whereas UDP- and dTDP-valienol were prepared from valienol 1-phosphate and UTP and dTTP, respectively, using RmlA-L89T, an engineered broad spectrum nucleotidyltransferase (Moretti et al, 2011), kindly provided by Prof. Jon Thorson at the University of Kentucky (Figures S2A and S2B). Although RmlA-L89T has been known to have relaxed substrate specificity towards various sugar phosphates (Moretti et al, 2011), the present study showed that RmlA-L89T is also able to process an unsaturated carbasugar phosphate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preparative glycosylation reaction was performed using 189 as the acceptor with the cloned rat kidney enzyme. A tetrasaccharide formed by the addition of a Glc pNAc residue (190) was the sole product detected (Scheme 22).…”
Section: International Journal Of Carbohydrate Chemistrymentioning
confidence: 99%
“…Compound 102 is then epimerized at C2 to give 5-epi-valiolone-7-phosphate (103). Further steps involving dehydration (104), carbonyl reduction and phosphorylations (105), nucleotidylation [190] (106), and final nucleophilic displacement by the nitrogen atom of 95 would afford compound 93 [191][192][193][194]. In Scheme 15, the transformation 105-106 constitutes a nucleotidylation reaction: the transfer of an entire nucleotidyl unit, rather than just a phospho group [195].…”
Section: Biosynthesis Of Acarbosementioning
confidence: 99%